The man from Halifax : Sir John Thompson, prime minister - Waite, Peter B. (Heritage., 1985)
Professor Waite has ably and intimately portrayed the private life of a late-Victorian politican: the sacrifice of home comforts, the loneliness of Ottawa, and the sense of public duty that drive Thomson, despite his natural inclinations, to persist in government service.